From Moral Teachings to Entertainment: Dysfunction of the “Pakem” Rules in Wayang Purwa Performances in the Contemporary Era - Bagong Pujiono; Iwan Budi Santoso; Dru Hendro; Tatik Harpawati (Universitas Gadjah Mada, 2026)
The dysfunction of the “pakem” rules in contemporary wayang purwa performances has become a significant phenomenon that has changed the face of this traditional art. Pakem, which should serve as a guideline for the narrative, characters, plot, dialogue, and ethics of the performance, has shifted from its role as an aesthetic standard toward more pragmatic and market-oriented considerations. This shift has caused the dysfunction of the “pakem” rules in wayang performances, which previously upheld traditions and noble values, to now be more oriented towards entertainment and market demands. This study aims to analyze the impact of the dysfunction of the “pakem” rules on the quality of wayang purwa performances in the contemporary era, focusing on three main aspects: the simplification of sulukan, the shift of authority from the dalang to guest stars, and extreme changes in performance style. Qualitative data obtained through in-depth interviews with puppeteers, musicians, and art observers were used to analyze this phenomenon. This analysis is also supported by relevant literature to provide a broader context for the changes occurring in puppetry practices. The results of the study show that the dysfunction of the “pakem” rules tends to influence the perceived quality of wayang performances, leading to the loss of the cultural and aesthetic depth that has been the identity of wayang purwa. This decline in performance quality also reflects a shift in orientation from moral teachings to mere entertainment. Therefore, further research is needed to enrich our understanding of wayang performances in the contemporary era, especially in efforts to revitalize pakem and reinforce traditional values in wayang performances.